Corporate Sustainable Development Through An Integrated Management System Approach: A Case Study of Corporate Sustainability Practice at PT. X Indonesia - Dafid, Dafid; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
a change in resource availability has been a concern of various parties. With the rapid economic growth in many parts of the world, global GDP is expected to increase from U.S. 70 trillion in 2008 to U.S. 135 trillion (increase 95%) in 2030. At the same time, the world population will grow from 6.7 billion people to 8.2 billion people. This phenomenon has prompted the more responsible and sustainable way to resource management, including resource management best-practice. Recent research from McKinsey suggests that the corporate sustainability practice has increased the ability of businesses to compete in the market. Recently, PT. X Indonesia has planned to implement corporate sustainable initiatives are more integrated, systematic, and continuous-based. Considering that corporate sustainability is a wide scope corporate initiative which involved many stakeholders both internal and external, PT. X Indonesia is very concerned about how to approach sustainability most effectively to gain sustainability competitive advantage through leverage their capabilities and will reduce future risk to sustainable growth of companyâ€™s business. The author has proposed the use of sustainability integration into business management systems through PDCA cycle of continuous improvement based on integrated management system approach. This solution would be basis to further develop PT. X Indonesia sustainability management practice in the areas of control, integration, and performance management. Implementation of final project is expected to optimize corporate sustainability initiatives to gain competitive advantage by ensuring their alignment to the achievement of business objectives and provide clarity and flexibility in managerial, measurement and assessment. The author has recommended implementation plan: establish objectives, prepare management programs, and monitoring progress in the last part of this document.Â Keyword: Corporate Sustainability, Integrated Management Systems, Business Management System, Organizational Capabilities, Stakeholders, Competitive Advantage.